The Performance of Teachers Perceptions in Interpersonal Communication in Elementary School Students in Medan City - Fachri Habib; Hasbih Soleh Suryadi; Agung Muhammad Nur; M Muflih Dermawan; Ahmad Rinaldi Siregar; Lucky Tirta Nurarfiansyah; Aswaruddin Aswaruddin (The Future of Education Journal, 2024)
Perception plays a crucial role in interpersonal communication, acting as the foundation for how individuals interpret and understand the messages they receive from others. Accurate perception enables clear communication, fostering mutual understanding and strengthening relationships, as it allows individuals to respond appropriately to the messages conveyed. On the contrary, inaccurate perceptions can result in misunderstandings, misinterpretations, and conflicts, often undermining the quality of communication. Various factors, such as personal experiences, cultural background, social context, and individual values, significantly influence how we perceive others and the situations we encounter. These influences can shape our attitudes and interpretations, sometimes leading to biased or distorted perceptions. For instance, our past experiences may lead us to make assumptions about others based on limited information, while cultural differences can affect how we interpret non-verbal cues or tone of voice. Thus, it is essential to develop self-awareness, which involves recognizing and reflecting on our own biases and perspectives. Active listening, which involves paying close attention to verbal and non-verbal cues and asking clarifying questions when needed, is also key in ensuring that we accurately perceive the messages others are trying to convey. Additionally, respecting and appreciating different points of view helps promote empathy and openness in communication, enabling individuals to understand and engage with others more effectively. By honing these skills, individuals can improve the accuracy of their perceptions, ultimately enhancing the quality of their interpersonal communication and fostering more positive and productive relationships.